Pengembangan Platform Pelatihan Programming DB2 berbasis Moodle menggunakan Successive Approximation Model (SAM) - Rafid Agung Pradana; Ahmad Afif Supianto; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Subunit certification Faculty of Computer Science University of Brawijaya is a facility that is used for improving their civitas skills. From an interview with the subunit head, Tri Afirianto stated that the subunit needs a training platform for DB2 that can be used to give information and helping the candidate for certification tests with learning matters. This study is focused on developing a training platform using Moodle. Moodle or Modular Object-Oriented Dynamic Learning Environment is one of the free learning management systems that can be used and developed by everyone dearly (open source). In the process, this study is using the Successive Approximation Model (SAM) as its learning design model.. This study of developing a DB2 programming training platform based on moodle with SAM will be tested its properness in every cycle on the model. The testing is to measure 2 categories of perceived usefulness (PU) and Perceived Ease of Use (PEUO) in the Technology Acceptance Model (TAM). This study will show how much the result of the product that comes out from developing method their perceived usefulness and perceived ease of use. The testing is done on 30 candidates which will be taking the certification. The result is the product has high ranked in category ease to use and high ranked in useful and helpful.